Between Rivers and Winds: Environmental Education and Community Art in Patagonia. Case Study: Crónicas de balsa (Huellas, 2026)
In 2014, Federico González launched Crónicas de balsa, an Environmental Education (EE) project based on building rafts from reused materials. Its main goal was to create a recycling network by connecting riverside communities across Argentine Patagonia through a river journey. The rafts transported not only waste but also ideas, motivations, and community initiatives, becoming floating stages for artistic interventions. This article presents Crónicas de balsa as an original, self-managed EE experience driven by, from, and for the community. The initiative weaves together art, nature, and environmental education to raise ecological awareness, foster community bonds, and promote local artistic expression. The first section describes the origins of the project. Next, it explores contributions from non-representational geographies (Thrift, 2007) and the affective turn, which help capture the sensitivity of relationships and the elements that shape a soundscape, as proposed by Raymond Murray Schafer (2013). Finally, the article narrates the experiences carried out and proposes an articulation between nature (particularly water and wind), art/music, and Law 27.621 on Comprehensive Environmental Education, drawing on Schafer’s (2013) concept of natural soundscapes.
Keywords: Natural Environment; Environmental Education; Art and Geography; Soundscapes; Non-Representational Theory